Implementation of the Sustainable Tourism Concept at Dempo Anailand Resort, Padang Pariaman Regency - Malik, Mirza A; Setiawan, Fadli; Firdaus, Firdaus (The Future of Education Journal, 2025)
This study aims to analyze the implementation of the sustainable tourism concept at Dempo Anailand Resort in Padang Pariaman Regency, West Sumatra. Using a descriptive qualitative approach and an inductive method, this research explores best practices, experiences, and challenges faced by the resort management in applying sustainability principles. Primary data were obtained through in-depth interviews with the management, local community, and tourists, while secondary data were gathered from documentation and supporting reports. The findings show that Dempo Anailand Resort has implemented the four main pillars of sustainable tourism: (1) sustainable destination management, (2) local economic utilization, (3) cultural preservation, and (4) environmental protection. Practical implementation is reflected in the use of renewable energy through solar panels, water conservation programs, integrated waste management, local community empowerment through economic partnerships, as well as cultural preservation and environmental education activities for tourists. However, the study also identifies several challenges, such as high implementation costs, low tourist awareness, and the need for support from the government and relevant institutions. Overall, the application of the sustainable tourism concept at Dempo Anailand Resort has had a positive impact on the economic, social, and environmental aspects. Increased tourist satisfaction, local community involvement, and management efficiency indicate that sustainable tourism can be an effective strategy for developing eco-friendly tourist destinations while improving the welfare of the surrounding community.